Neoadjuvant pazopanib in nonrhabdomyosarcoma soft tissue sarcomas (ARST1321): A report of major wound complications from the Children's Oncology Group and NRG Oncology. Issue 5 (13th February 2023) - Kayton, Mark L.; Weiss, Aaron R.; Xue, Wei; Binitie, Odion; Hayes Dixon, Andrea; Randall, R. Lor; Sorger, Joel I.; Hawkins, Douglas S.; Spunt, Sheri L.; Wang, Dian; Million, Lynn; Terezakis, Stephanie; et al.
Abstract: Background and Objectives: The impact upon wound healing of targeted molecular therapies, when incorporated into neoadjuvant therapy of soft tissue sarcoma, is largely unknown. Here, we describe wound complications following addition of pazopanib, a tyrosine kinase inhibitor (TKI), to neoadjuvant radiotherapy (RT) +/− chemotherapy for soft tissue sarcoma. Methods: Wound complications were evaluated on dose‐finding and randomized arms of ARST1321, a phase II/III study incorporating neoadjuvant RT,  +/− pazopanib, +/− ifosfamide/doxorubicin (ID) for sarcoma therapy. Results: Of 85 evaluable patients, 35 (41%) experienced postoperative wound complications. Most (57%) were grade III. Randomization to pazopanib + RT + ID carried a 50% wound complication rate (17/34, with 47% grade III), compared to 22% (5/23) with ID + RT alone. In nonchemotherapy study arms, pazopanib + RT resulted in a 59% wound complication rate versus 25% for those receiving RT alone. Grade III wound complications occurred among 26% (15/58) of all patients receiving pazopanib. Wound complications occurred a median of 35 days postoperatively. Some occurred following diagnostic biopsies and at remote surgical sites. Conclusion: The addition of pazopanib to neoadjuvant chemotherapy and RT resulted in a higher wound complication rate following therapy of soft tissue sarcoma. The rate of grade III complications remained comparable to that reported in contemporary literature.